Effect of strain rate on hydrogen embrittlement in low-carbon martensitic steel. (2nd February 2017) - Momotani, Yuji; Shibata, Akinobu; Terada, Daisuke; Tsuji, Nobuhiro
Abstract: This study investigated the effect of strain rate on hydrogen embrittlement behavior in a low-carbon martensitic steel. Elongation of the hydrogen-charged specimen decreased significantly with decreasing the strain rate. The characteristics of the hydrogen-related fracture behavior also changed with the strain rate. Hydrogen micro-print technique and electron backscattering diffraction analysis revealed that the deformation at a lower strain rate facilitated hydrogen to accumulate mainly on prior austenite grain boundaries. This hydrogen accumulation led to the formation of micro-cracks along prior austenite grain boundaries and brittle fracture on or in the vicinity of prior austenite grain boundaries. On the other hand, in the case of a higher strain rate, micro-cracks formed mainly inside prior austenite grains and transgranular fracture occurred. This is presumably because there was not enough time for hydrogen to accumulate on prior austenite grain boundaries during tensile test. Graphical abstract: Highlights: HE of a 0.2C martensitic steel increased with decreasing strain rate (SR). H-related fracture changed from transgranular to intergranular with decreasing SR. Deformation at lower SR facilitated H to accumulate mainly on PAGB. The H accumulation at PAGB led to brittle fracture on or in the vicinity of PAGB.